Adaptive trial for the treatment of depressive symptoms associated with concussion using accelerated intermittent theta burst stimulation (ADEPT): rationale, design and methods - Oberman, Lindsay M.; Penafiel, Adriana I.; Dieterich, Rachel; Phan, Cuong T.; Chou, Yi-Yu; Pham, Dzung L.; Adamson, Maheen M.; Hines, Christopher E.; Rezaee, Zeynab; Deng, Zhi-De; Pal, Hemant; Lisanby, Sarah H.; et al. (Frontiers in Neurology, 2025)
Military service members (SMs) and veterans who have sustained one or more concussions during their service have significantly higher rates of persistent depressive symptoms and suicidality compared to non-injured peers. Despite over 500,000 SMs who have sustained concussions, there are currently no Level I evidence-based treatments for improving depressive symptoms associated with concussion. Accelerated intermittent theta burst stimulation (aiTBS), a specific repetitive transcranial magnetic stimulation (rTMS) protocol, targeted at the dorsolateral prefrontal cortex (DLPFC) has demonstrated efficacy and is cleared for the treatment of Major Depressive Disorder (MDD) by the United States Food and Drug Administration (FDA). The mechanism of action of aiTBS is thought to be via the modulation of functional networks. Herein we outline the design of a multisite, double-blind, randomized, sham-controlled trial of aiTBS for the treatment of depressive symptoms in SMs and veterans with a history of concussion. We present the rationale for this specific design and highlight the potential for personalized neuroimaging-informed parameter determination in this population where brain injuries have resulted in variable structural and functional brain circuitry disruptions. If successful, this project will accelerate solutions to improve the health, well-being, and healthcare of SMs and veterans with depressive symptoms following concussion.Clinical trial registrationClinicaltrials.gov, NCT05426967.